Social cohesion in the context of environmental/climate-related internal displacement in Ghana - Susan Ekoh; Charles Martin-Shields; Carolin Kitzmann; Nina Küssau; Mario Pfeffer; Merle Platen; Theresa Reinel; Mary Boatemaa Setrana; Johnson Wilson Appiah Kubi; Stella Effa (German Institute of Development and Sustainability (IDOS), 2025)
Climate change poses an existential threat to individuals and communities across the world. Populations with existing socio-economic vulnerabilities are the most affected, with people already experiencing climate-related losses and damages. Extreme weather events and other adverse impacts of climate change lead to forced displacement of populations to, from and within cities. Hence, building and supporting social cohesion in displacement contexts will be a key activity for development cooperation actors. This research study therefore explores these questions: How do the elements of social cohesion, trust, inclusive identity and cooperation for the common good, evolve within communities and across institutions in Accra's informal settlements? Additionally, what role do climate resilience efforts play in fostering or hampering vertical and horizontal social cohesion in Accra's informal settlements?Our findings suggest that limited institutional resilience efforts contribute to weak vertical cohesion between neighbourhoods and city authorities, undermining collective responses to climate challenges. The research emphasizes the need for a more integrated approach, whereby community-led initiatives and state interventions work together to strengthen resilience and social cohesion in Accra's informal settlements.
Keywords: 320; Urban Displacement; Social Cohesion; Climate Change; Ghana; Accra